Philosophical positions of Hegel and Danto on "the end of art" - Domínguez Hernández, Javier (Estudios de Filosofía, 1996)
Both, the position of Hegel and that of Danto, are not only historiographical but also philosophical: the former is concerned with art in Modernity, and the latter, in Postmodernity. For Hegel the "end of art" does not mean the end at all, but a radical change of function of the figures of truth that art has to share with religion and philosophy in modern times. The classical representation of truth as absolute gives up to the romantic one. For Danto, on the other hand, the "end of art" means that art enters in a posthistoric epoch, since history of art is no longer based on its inner necessity of constant change, and postphilosophical, since thought has turned art into a cognitive praxis of selfthinking which makes it similar lo philosophy.